COMPARING PHILOSOPHIES OF LANGUAGE EDUCATION: PROGRESSIVISM AND PERENNIALISM - Darwanto, Agus (Conscientia - Journal on Language, Literature, and Culture, 2025)
This is a comparative study of two, amongst others, major educational philosophies—Perennialism and Progressivism—focusing on their respective characteristics: their views of reality, epistemological positions, and, more specifically, their implications for education. Each philosophy offers a unique perspective while sharing certain fundamental principles in shaping student development. Perennialism emphasizes timeless truths and the development of intellectual and moral virtues through classical works and structured learning. Progressivism, in contrast, focuses on experiential learning, a student-centered approach, and adaptability to changing societal needs. After understanding the similarities and differences within these philosophies, this study also explores the contributions and limitations of each within the broader context of language learning and educational practice.